Fictive and fictitious diseases in La guerra silenciosa, by Manuel Scorza - Huamanchumo de la Cuba, Ofelia (2019)
In the narrative world of the five novels in the series La guerra silenciosa, certain circumstances are depicted as unfavorable to the main characters, to particular groups,to entire communities, to animals, and even to geographical entities, on a social, economic and geopolitical level, as if they were 'diseases'. These include the illness of invisibility,centuries of insomnia, and an epidemic of color blindness, among others, and they can be understood as fictive diseases and grouped for analysis into two categories: (a)fictive diseases with a correlation to reality; (b) fictive and fictitious diseases without a correlation to reality. The main goal of this article is to describe these disorders, afflictionsand ailments from the perspectives of medical science and literary theory, in order to outline the narratological functions they perform within Scorzian fiction, namely:the use of irony and humor as discursive resources within a literature of social denunciation.